Copper Cold Gas-Dynamic Spray Processing for Highly Effective Antipathogenic Coatings: An Integrated Microstructural, Mechanics, and Materials Chemistry Perspective - Bryer C. Sousa; Danielle L. Cote (Current Perspectives on Chemical Sciences Vol. 9, 2021)
The impetus behind this effort centers upon the improvement of a more robust understanding of the microstructural qualities, materials surface, and bulk chemistry, as well as properties of cold sprayed conventional copper and nanostructured copper coatings, in so far as they relate to antipathogenic contact killing and inactivation applications. Therefore, the role of high strain rate induced severe plastic deformation states, microstructures, electrochemical behaviors, surface chemistry, and surface roughness were characterized for two copper cold spray material consolidations, which were produced from conventionally gas-atomized copper powder as well as a nano-agglomerated and spray-dried copper feedstock powder, during this work. Prior work has revealed greater antipathogenic efficacy concerning the respective nanostructured Cu coating versus the conventional Cu coating. Thus, the microstructural analysis was performed to establish differences between the two coatings such that their respective pathogen killing and/or inactivation rates could be deductively and experimentally attributed to. Results from advanced laser-induced projectile impact testing, X-ray diffraction, scanning electron microscopy, electron backscatter diffraction, scanning transmission microscopy, nanoindentation testing, energy-dispersive X-ray spectroscopy, confocal microscopy, atomic force microscopy, linear polarization, X-ray photoelectron spectroscopy, electrochemical impedance spectroscopy, and copper ion release assessment, among other experimental methods, were performed and pursued during the research and results considered herein.